Wells Turbine for Wave Energy Conversion for Malaysian Ocean - Ahmed, Yasser M.; Yaakob, O. B.; Elbatran, A. H.; Mazukee, U. J. A. (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2014)
Malaysia is surrounded by ocean, therefore Malaysia is a perfect candidate for harvesting ocean energy as electrical generator to distribute to main grid. Malaysian electrical generation still greatly influences by non-renewable energy and the electrical cost increase as the natural resource depleting. The only solution for this problem is to use renewable energy, due to geography of Malaysian land which surround by ocean; ocean energy is the best renewable energy for Malaysia. One method of converting this energy is to use Oscillating Water Column using wells turbine as converter from pneumatic energy to mechanical energy thus convert by generator to electrical energy. However, wave characteristic of Malaysian ocean make conversion of wave energy really difficult.Some parameter that affect the performance of wells turbine need to be changed, so the new geometry turbine can work effectively in Malaysian ocean of the poor ocean characteristics such as low wave high and low frequency. According to Malaysian wave data, the average wave height is from 0.5m to 1.5m with average wave frequency of 0.1 to 0.3Hz and wave period 3.34s to 10s.